(untitled) (Journal of Engineering, 2011)
Lowering the emission, fuel economy and torque management are the essential requirements in the recent development in the automobile industry. The main engine control input that satisfies the above requirements is the throttling angle which adjusts the air mass flow rate to the engine port. Due to the uncertainty and the presence of the nonlinear components in its dynamical model, the sliding mode control theory is utilized in this work for the throttle valve angle control system to design a robust controller for this system in the presence of a nonlinear spring and Coulomb friction. A continuous sliding mode control law which consists of a saturation function, instead of a signum function, and the integral of another saturation function is used in this work. This choice for the control structure will prevent the chattering to occurs but with a certain steady state error. On the other hand, the addition of the integral term will effectively reduce the steady state error according to the choice of its parameters. The simulations result for typical references of the opening throttle angle demonstrate the effectiveness of the proposed controller, especially after the addition of a nonlinear integral term.